Distribution and Health Risk Assessment of Some Trace Elements in Runoff from Different Types of Athletic Fields - Xiaoran Zhang; Yinrui Wang; Junfeng Liu; Yucheng Jiang; Yiran Tian; Ziyang Zhang (Journal of Chemistry)
Environmental risk of heavy metals and metalloids in athletic fields has raised people’s attention in the recent years. Seven trace elements, including metals and metalloids, were detected in the runoff of five typical athletic fields in the university campus under three rainfall events. Except for Cr, the total concentrations of Zn, Pb, Cu, Mn, Cd, and As in artificial turf runoff are the highest among five athletic fields, followed by that of plastic runway. The concentration and first flush effect of trace elements are followed in the order of 1st > 2nd > 3rd rainfall events. The strongest correlations between metals and metalloids were observed in the tennis court runoff, while the artificial turf shows the least. The release of trace elements could be directly from the surface materials and particles on the athletic field and influenced by the comprehensive factors including surface materials, rainfall events, and pollutant characters. Pollution risk assessment shows that the pollution extent of the five types of athletic field is at least “moderate” and follows the order of artificial turf > basketball court > plastic runway > badminton court > tennis court. Pb shows the highest pollution level, while Cr shows the highest healthy risk. The results can provide a theoretical basis for runoff pollution control and safety use of athletic fields.